Yahoo Web Search

  1. Sort by

  1. LHS = (-2)^x / 2^x = (-1 * 2 )^x / 2^x = (-1)^x * 2^x / 2^x = (-1)^x

    2 Answers · Science & Mathematics · 03/04/2012

  2. LHS: Top: tan²θ + 1 = sin²θ/cos²θ + 1 = sin²...

    5 Answers · Science & Mathematics · 16/05/2007

  3. LHS: The numerator is the difference of perfect quares, hence, ...

    4 Answers · Science & Mathematics · 15/04/2007

  4. LHS = tan x + cot x ...... = ( s/c ) + ( c/s ) ...... = ( s² + c² ) / ( sc...

    3 Answers · Science & Mathematics · 25/01/2010

  5. LHS = 2 cot x / (1+ cot^2 x) = 2 cot x/ (cosec ^2 x) = 2 cos x/ sin x/(1/ sin ^2 x) = 2 cos x sin x = sin 2x

    2 Answers · Science & Mathematics · 30/09/2012

  6. LHS = cos²A.sec²A + cos²A.secA + cos²A 1...

    1 Answers · Science & Mathematics · 11/01/2014

  7. LHS = cos x tan^3x=sin x tan^2x = cosx[sin^3x/cos^3x] = [cosx/cos^3x]*[sinx*sin^2x] = [ 1/cos^2x]*[sinx*sin^2x] = sinx[sin^2x/cos^2x] = sinx tan^2x = RHS

    2 Answers · Science & Mathematics · 05/05/2014

  8. ... LHS = ( csc ) ( 1 - cos ) = ( 1 / sin ) ( 1 - cos ) = [ ( 1 - cos ) / ( sin ) ] • [ ( 1 + cos...

    2 Answers · Science & Mathematics · 21/12/2011

  9. LHS d/dt[a-(v*r)]=da/dt -r*dv/dt -v*dr/dt d/dt[a-(v*r)]=da/dt -r*a -v^2 RHS a*(v*r) I can't prove it.

    2 Answers · Science & Mathematics · 25/09/2007

  10. LHS=-sin2x - 2(1-cos2x) = -sin2x + 2cos2x - 2 = asin2x + bcos2x + c , a=-1 , b=2 , c=-2

    2 Answers · Science & Mathematics · 27/05/2013

  1. Try asking your question on Yahoo Answers